EVALUATING THE QUALITY OF MAWARIS AKM (MINIMUM COMPETENCY ANALYSIS (AKM) ITEMS USING RASCH MINISTEP MODELING: LITERACY AND NUMERACY - Maulidia, Sofia; Putranta, Hilmawan (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2025)
Item quality analysis is crucial for enhancing student capabilities and the overall quality of educational practices. The objective of this study is to analyze and delineate the quality of items associated with the Minimum Competency Assessment of Mawaris material utilizing the Rasch ministep model, thereby providing recommendations aimed at improving assessment questions to better achieve educational objectives. This research uses a quantitative descriptive approach with an evaluative focus. Data collection was executed through documentation techniques, specifically using an instrument comprising 10 AKM questions pertaining to Mawaris material, distributed to Islamic Religious Education students at UIN Sunan Kalijaga during the 2024/2025 academic year. The instrument encompassed 5 literacy questions and 5 numeracy questions. The findings indicate that out of all the questions evaluated, only 8 attained the standards of validity. Based on item estimation, item reliability was calculated at 0.81, which is regarded as exhibiting good reliability, whereas the person estimation yielded a reliability score of 0.00, which is considered weak. The analysis revealed that 7 items functioned effectively for distractor efficacy, while 3 items failed to perform adequately. Furthermore, the difficulty analysis of the evaluated items illustrates a proportional variation in the complexity of the questions.